Income Analysis of Meubel Industrial Entrepreneurs in Palopo City, South Sulawesi - I Ketut Patra; Risna Risna (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
The development of the furniture industry is part of a long-term effort to change a strong and balanced economic structure. With the furniture industry, society can be more advanced and developed. On the other hand, the local government should develop the main economic potential, namely the furniture craft industry such as cabinets, chairs, tables and various other household furniture. The furniture industry must increase its production capacity, which requires a large amount of capital. This study aimed to determine whether capital, number of workers, length of business affect the income of the Furniture Industry in Palopo City. The type of data related to this research is quantitative data sourced from primary data. This research was conducted on the Furniture Industry Entrepreneur in Palopo City. This study indicates that the variables of capital and labour affect the income of furniture industry entrepreneurs in Palopo City. At the same time, the variable length of business does not affect the income of furniture industry entrepreneurs in Palopo City